An injectable and pH-responsive hyaluronic acid hydrogel as metformin carrier for prevention of breast cancer recurrence. (15th March 2023) - Zheng, Zexiang; Yang, Xing; Zhang, Yifan; Zu, Weiqiang; Wen, Minna; Liu, Taisheng; Zhou, Changren; Li, Lihua
Abstract: To achieve the pH-responsive release of metformin in tumor acidic microenvironment, we prepared OHA-Met by covalently grafting metformin (Met) onto oxidized hyaluronic acid (OHA) through imine bonds, and then prepared carboxymethyl chitosan (CMCS)/OHA-Met drug loaded hydrogels. The CMCS/OHA-Met hydrogels showed the in-situ injection performance. At pH = 7.4, the cumulative release rate of metformin from CMCS/OHA-Met20 hydrogel was 42.7 ± 2.6 % in 6 h, and the release tended to balance after 72 h. At pH = 5.5, the release kept constant and the cumulative release rate was 79.3 ± 4.7 % at 6 h, showing good pH-responsive behavior. Metformin induced apoptosis of MCF-7 cells through the caspase 3/PARP pathway. CMCS/OHA-Met20 hydrogel could effectively kill MCF-7 cells, while reducing the cytotoxicity of free metformin to L929 cells. In vivo breast cancer recurrence experiments showed CMCS/OHA-Met20 hydrogel could achieve local injection and pH-responsive smart drug delivery at the tumor resection site, inhibiting breast cancer recurrence. Compared with direct administration, CMCS/OHA-Met20 hydrogel reduced the metformin dosage, frequency of administration and systemic side effects. Graphical abstract: Unlabelled Image